Silencio, murmullo, ruido: El derecho, el lenguaje y la literatura de Borges - Ana Dobratinich, Héctor Gonzalo (2019)
[Noises, murmurs and silences. Law, language and literature in Borges] Noises, murmurs and silences reside in every stroke printed by literary and legal writing. The space that whispers in the absence, is perhaps the one that the legal language must grasp and constantly expand in each epistemological proposal. Able to expose and strip us, literature invites us to read Borges. It will be a game, a digression, a dialogue or a neutral space between what is and what ought to be. The mere fact of transiting requires a resignification of the legal space, even if by doing so we invoke foreign noises, mythological murmurs or simply our own silences.